Community service learning with first peoples - Bartleet, B.; Bennett, Dawn; Power, A.; Sunderland, N. (2018)
© Oxford University Press 2018. All rights reserved. Community music educators worldwide face the challenge of preparing their students for working in increasingly diverse cultural contexts. These diverse contexts require distinctive approaches to community music-making that are respectful of, and responsive to, the customs and traditions of that cultural setting. The challenge for community music educators then becomes finding pedagogical approaches and strategies that both facilitate these sorts of intercultural learning experiences for their students and that engage with communities in culturally appropriate ways. This chapter unpacks these challenges and possibilities, and explores how the pedagogical strategy of community service learning can facilitate these sorts of dynamic intercultural learning opportunities. Specifically, it focuses on engaging with Australian First Peoples, and draws on eight years of community service learning in this field to inform the insights shared.